Synthesis of Sheet‐like Zeolite TS‐1 with Short b‐Axis for Epoxidation of 1‐Hexene. Issue 10 (9th March 2023) - Zhang, Min; Ren, Shenyong; Guo, Qiaoxia; Shen, Baojian
Abstract: In zeolite TS‐1, the straight channel parallelled to the b‐axis direction has larger pore size and thus is main diffusion channel for molecules. Shorter b‐axis brings about shorter diffusion channel, which can leads to higher adsorption and diffusion rate. Therefore, with regard to the morphology modification of MFI zeolites, many studies touch on short b‐axis zeolites have been reported. Unfortunately, most of the preparation processes require harsh synthesis conditions and complex organic templates, and they are not conducive to large‐scale applications. In this work, cheap organic additive urea and seed crystals were added to synthesize sheet‐like TS‐1, which boasts short b‐axis. At the same time a pre‐crystallization was performed at the aging solution stage. In the b‐axis direction, the zeolite TS‐1 prepared in this way had a minimum thickness of about 50 nm. This is because urea can inhibit the growth of crystals in the b‐axis direction, and the guiding effect of the seed liquid also plays the function of adjusting the b‐axis thickness. In the epoxidation of 1‐hexene with H2 O2 when catalyzed by sheet‐like TS‐1, the selectivity of the target product 1, 2‐epoxyhexane was significantly improved. Abstract : Sheet‐like zeolite TS‐1 was synthesized under hydrothermal conditions by adding seed and urea. Liquid seed and pre‐crystallization could adjust thickness of sheet‐like sample in b‐axis direction. Epoxidation of 1‐hexene with H2 O2 catalyzed by sheet‐like TS‐1 gave high selectivity of 1, 2‐epoxyhexane.